The Influence of Leadership Style and Empowerment on Efficiency Virtual Teams Mediated by Trust - Triyani Triyani; Muhammad Sadikin; Justine Tanuwijaya; Stefanus Sadana (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research aims to analyze the influence of leadership style and empowerment on the virtual efficiency of it industry employees in Indonesia. Analyzing the trust's role in mediating transformational leadership and transactional leadership and empowerment towards the virtual efficiency of the IT industry employee in Indonesia. The data analysis method used in this study is the structural equation model (SEM) using the Lisrel program.  This research uses an inferential statistical approach, namely testing the influence hypothesis between variables and Structural Equation Modeling (SEM) where variable trust plays a role in mediating the influence of leadership and empowerment on employee performance and job satisfaction. The results of this study show that the Judge must make a decision that is wise and fair in handling each case, especially with regard to notary deed. Every deed made by a Notary must meet: material and formal needs. The notary must be ready and responsible for every deed product he makes, whether civil, criminal or administrative.